Property maintenance of Campbell shopping complex / Muhammad Rosli Zakaria ... [et al.] - Zakaria, Muhammad Rosli; M. Noor, Haswandi; Abdullah, Norazlan; Mat Yaakub, Suraida (2000)
Maintenance management requires a variety of skills including the technical knowledge and site experience to identify maintenance need and to specify remedies an understanding of modern techniques of business management knowledge of the law as it affects property and contracts and perhaps most important of all understanding of people and their needs, since the vast majority of building exist to shelter human beings in their homes and workplaces.